Potent Anti-amoebic Effects of Ibogaine, Voacangine and the Root Bark Alkaloid Fraction of Tabernaemontana arborea - Carrero, Julio César; Curay-Herrera, Violeta; Chacón-Niño, Lysette; Krengel, Felix; Guzmán-Gutiérrez, Silvia-Laura; Silva-Miranda, Mayra; González-Ramírez, Luisa-Carolina; Bobes, Raúl J.; Espitia, Clara; Reyes-Chilpa, Ricardo; Laclette, Juan-Pedro (Planta Medica, 2022)
Plants of Tabernaemontana species have several pharmacological activities including antimicrobial effects. Amoebiasis continues to be a public health problem, with increasing evidence of resistance to metronidazole. In this study, we assessed the effect of the alkaloid fraction of T. arborea root bark and the alkaloids ibogaine and voacangine on the viability and infectivity of Entamoeba histolytica trophozoites. Cultures were exposed to 0.1 – 10 µg/mL for 24, 48 and 72 h, and viability was then determined using a tetrazolium dye reduction assay and type of cellular death analyzed by flow cytometry. Results showed that the alkaloid fraction, but mainly ibogaine and voacangine alkaloids, exhibited potent dose-dependent anti-amoebic activity at 24 h post-exposure (IC50 4.5 and 8.1 µM, respectively), comparable to metronidazole (IC50 6.8 µM). However, the effect decreased after 48 and 72 h of exposure to concentrations below 10 µg/mL, suggesting that the alkaloids probably were catabolized to less active derivatives by the trophozoites. The treatment of trophozoites with the IC50 s for 24 h induced significant morphological changes in the trophozoites, slight increase in granularity, and death by apoptonecrosis. The capacity of T. arborea alkaloids to inhibit the development of amoebic liver abscesses in hamsters was evaluated. Results showed that even when the treatments reduced the number of amoebic trophozoites in tissue sections of livers, they were unable to limit the formation of abscesses, suggesting their rapid processing to inactive metabolites. This work leaves open the possibility of using Tabernaemontana alkaloids as a new alternative for amoebiasis control.
Keywords: Entamoeba histolytica; Tabernaemontana arborea; Apocynaceae; ibogaine; voacangine; alkaloids; anti-amoebic; amoebic liver abscess